A cross‐linguistic study of multisensory perceptual narrowing in German and Swedish infants during the first year of life. Issue 2 (9th January 2021) - Dorn, Katharina; Cauvet, Elodie; Weinert, Sabine
Abstract: Four‐and‐a‐half‐month‐olds look longer at silent mouth movements corresponding to a language they previously listened to. The perceptual narrowing hypothesis suggests this general ability to decline as a consequence of experience with the infant's native language. We tracked eye‐gaze of German and Swedish infants longitudinally in an intersensory matching procedure at 4.5 and 6 months of age. Infants watched and listened sequentially to side‐by‐side presentations of visual and corresponding auditory fluent speech in their respective native or the non‐native language. Looking times indicated that 4.5‐month‐old infants preferred the respective language they previously listened to, either native or non‐native. However, at 6 months of age they only audio‐visually matched their native language and kept looking at chance level after listening to the non‐native language – suggesting that the intersensory perception of languages narrows down before 6 months of age even in same‐rhythm‐class languages. Intriguingly, the 6‐month‐old German and Swedish samples showed different patterns of preference after listening to their native language. Whereas the German infants looked significantly longer to the German visual speech, the Swedish infants looked significantly shorter to the Swedish visual speech. Different explanations and practical implications for early hearing aids are discussed within the frame of perceptual narrowing. Highlights: First study to examine perceptual narrowing in same‐rhythm‐class languages. In an intersensory matching procedure audio‐visual matching of languages narrows down before 6 months of age in same‐rhythm‐class languages. The empirical findings might have crucial practical implications for early hearing aids.